The distance from the holomorphically decomposable Fredholm spectrum - Abdelaziz Tajmouati; Mohamed Baba Mohamed Ahmed; Abdeslam El Bakkali (Boletim da Sociedade Paranaense de Matemática, 2019)
The class of holomorphically decomposable Fredholm operators was introduced by A. Tajmouati and A. El Bakkali since subclass of Saphar operators. Several authors have been interested in the distance of spectrum associated with the different classes. Especially C. Schmöeger has calculated the distance of Saphar spectrum. For this reason, in this paper, we establish the distance of the holomorphically decomposable Fredholm spectrum.